ANALISIS SEMIOTIKA ROLAND BARTHES TERKAIT ISU PEREMPUAN PADA KONTEN DAKWAH TIKTOK @KADAMSIDIK00 - Rahmi, Lailatur; Rasyid, Anuar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Da'wah is a fundamental thing in Islam, and is a form of communication in society that aims to spread Islamic religious messages. The @kadamsidik00 tiktok account is one of the preachers who utilizes social media as a means of da'wah, especially for the younger generation. This study aims to analyze the meaning of denotation, connotation and myth related to women's issues in the @kadamsidik00 tiktok account. This research uses qualitative research methods using Roland Barthes' semiotic theory. The subjects in this study are videos on the women's issues playlist on the @kadamsidik tiktok account. Data collection techniques using documentation techniques and literature studies. The analysis is carried out starting from looking for denotation meaning, then connotation and then relating to myths based on video pieces and messages that have been selected. The results showed that the denotation meaning in Husain's video content is the general description and message content of the video delivered by Husain in delivering his da'wah. The connotation meaning in the video content is in the form of appearance, voice intonation, and the meaning behind the message conveyed by Husain regarding women's manners, responsibility, and maintaining lust and continuing to follow Allah's commands. Thus forming myths in the form of messages that are believed by the public visually and verbally. Keywords: Semiotics; Roland Barthes; Women's Issues; Da'wah; Tiktok